Reaction of planktonic and benthic algae in the Black Sea to the consequences of the destruction of the Kakhovska Reservoir dam on the Dnipro River (Ukraine) - Minicheva, G.G.; Garkusha, O.P.; Kalashnik, K.S.; Marinets, G.V.; Sokolov, Y.V. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2024)
The paper presents the results of study of the effects of the destruction of the Kakhovka dam on the Black Sea phytoplankton and phytobenthos. As a result of dam blast, unprecedented event took place: a huge volume of fresh water with a high concentration of nutrients and pollutants was dumped into the marine ecosystem. Field observations were conducted in the coastal zone of the Odesa Bay and in the open part of the northwestern part of the Black Sea (NWPB) using satellite technologies, in the period of June–August 2023. The object of research were communities of phytoplankton, micro- and macrophytobenthos. The metods include classical indices of marine algae assessment, analysis of satellite data and a holistic approach using universal morpho-functional indicators. The highest values both of chlorophyll a concentration and the ratio of water bloom area to the total area of the Ukrainian sector of the NWPB were recorded from the middle to the end of July 2023. For coastal phytoplankton, the maximum values of quantitative quantitative indicators of diatoms were noted one week after the catastrophe, of cyanoprokaryotes – two weeks later. Functioning of algae with different ecological activity (S/W of phytoplankton – 964.9, microepiphyton – 542.6, macrophytes – 80.9 (m2∙kg-1) optimizes the mechanism of restoration of the marine ecosystem to the state before the disaster. Temporary wave-like outbreaks of the development of planktonic and benthic algae in conditions of unlimited availability of nutrients in the marine environment were revealed. The half-period of the wave of phytoplankton growth according to the value of the Surface Index (SI, unit) is reached in approximately 3 weeks. In the maximum phase of water bloom the development of macrophytobenthos is inhibited As the intensity of the bloom fades, the conditions for the further development of benthic macroalgae are restored. The half-period of the wave of phytobenthos development (according to the IP value) is approximately 5 weeks.